Analysis of The Use of Punctuation Marks on The Writing Ability of Nursing Students - ASEF WILDAN MUNFADLILA (Prodi Tadris Bahasa Inggris, 2022)
language skills are the main capital in writing skills. The writing ability of university students is the basic for language skills to the next level or level. The ability to use correct spelling is one of the important things in writing skills. The research design used a qualitative descriptive approach, because this study aims to describe the use of punctuation in writing explanatory texts for 2nd semester 4th grade students of the S1 Nursing Study Program, STIKES Bina Sehat PPNI Mojokerto. This study is intended to collect data, manage data, analyze data and present data objectively regarding the object of research, namely the use of punctuation in writing explanatory texts for level 2 semester 4 of the S1 Nursing Study Program, STIKES Bina Sehat PPNI Mojokerto. Based on the result The total number of punctuation errors as many as 207 out of 45 students writing explanatory texts shows that the intensity of punctuation errors is still high enough so that improvements and improvements are needed in the learning process.